2022
DOI: 10.1186/s12944-022-01766-z
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of low serum lipoprotein cholesterol on the immune microenvironment in gastric cancer: a case‒control study

Abstract: Background Cholesterol is crucial for tumor immune microenvironment (TIME) remodeling. Serum lipoprotein cholesterol is closely associated with gastric cancer (GC) progression, but whether it affects TIME remodeling is unknown. Methods GC patients with differential serum high-density lipoprotein (HDL) or low-density lipoprotein (LDL) cholesterol levels were collected. After balancing the baseline, immunohistochemical staining was performed on seria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The TIME of each tumor was divided into two immune compartments, the TLS zone and the extra-TLS zone, which were assessed independently, as described previously [28]. Briefly, TLS locations were classified into intratumoral (those surrounded by tumor cells), stromal (those surrounded by tumor stromal cells), and peritumoral (those located between tumor and normal tissues) types.…”
Section: Methodsmentioning
confidence: 99%
“…The TIME of each tumor was divided into two immune compartments, the TLS zone and the extra-TLS zone, which were assessed independently, as described previously [28]. Briefly, TLS locations were classified into intratumoral (those surrounded by tumor cells), stromal (those surrounded by tumor stromal cells), and peritumoral (those located between tumor and normal tissues) types.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies demonstrated that cholesterol served a crucial function in remodeling tumor immune microenvironment ( Figure 2D ). 62 Specifically, the membranal cholesterol level influences T-cell activity and function, 63 and downstream cholesterol products are essential for B-cell migration. 64 A study reported in “Nature” suggested that inhibiting PCSK9, a protein that regulates cholesterol metabolism, could promote tumor response to immune-check-point therapy by enhancing major histocompatibility complex class I protein expression on the surface of tumor cells.…”
Section: Cholesterol-related Tumorigenesis and Progressionmentioning
confidence: 99%